Pengaruh Brand Image dan Brand Awareness Terhadap Keputusan Pembelian Pizza Hut Delivery Cabang Plaju - Meilani, Windi; Rosa, Aslamia (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effect of brand image and brand awareness on purchasing decisions for pizza hut delivery at the Plaju branch. This study used a quantitative approach with data collection methods through questionnaires. The population in this study were people in Palembang City aged 15-25 years who had purchased pizza hut delivery from the Plaju branch in October, November, December 2022 and January, February, March 2023. The sampling method used purposive sampling with a total sample of 100 respondent. Data analysis techniques in this study were hypothesis testing, coefficient of determination testing, and multiple linear analysis. the results of testing the calculated F value of 73,597 with a significance value of 0.000 (0.000 <0.05), brand image and brand awareness together have a positive and significant effect on purchasing decisions for Pizza Hut Delivey Plaju Branch. Keywords: Brand image, Brand Awareness, Purchase Decisions